IMPACT OF GREEN ECONOMICS ON CARDIOVASCULAR HEALTH MANAGEMENT IN KASHMIR: A SUSTAINABLE APPROACH - Syed Mohd. Faisal Qadri; Mohd. Faisal Khan; Sakhi John; Noria Farooqui (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Cardiovascular diseases (CVDs) are the leading cause of mortality worldwide, and the Kashmir region of India is no exception, where the prevalence of CVDs is alarmingly high. The unique environmental, socio-economic, and cultural aspects of the region pose challenges for the effective management and prevention of CVDs. In recent years, the concept of Green Economics has emerged as a novel approach to integrating sustainability into economic and health policies. This study explores the potential impact of Green Economics on the management of cardiovascular health in Kashmir, focusing on the sustainable integration of environmental, economic, and health factors to address CVDs. By examining the intersection of green policies, healthcare systems, and environmental health, this paper proposes a comprehensive framework that advocates for eco-friendly practices, improved healthcare infrastructure, and socio-economic reforms. The findings indicate that adopting Green Economics can enhance the quality of cardiovascular care, promote healthier lifestyles, and reduce the environmental determinants contributing to CVDs in Kashmir.